A sorted leading indicators dynamic (SLID) factor model for short-run euro-area GDP forecasting - Grenouilleau, Daniel; European Commission : Directorate-General for Economic and Financial Affairs (Brussels ; Belgium : European Commission: Directorate-General for Economic and Financial Affairs, 2004)
This paper introduces a statistical model for short-term GDP forecasting based on approximate dynamic factors, Stock and Watson methodology, extracted from a very large number of leading indicators at several lags. Given that factor extraction is performed on many series from all countries of the euro area, the common component to all predictors reflects the overall business cycle of the euro area and can accordingly provide a good proxy for euro area GDP.
Internal paper
Economic Papers